2015
DOI: 10.1007/s13277-015-4468-x
|View full text |Cite
|
Sign up to set email alerts
|

Desacetyl nimbinene inhibits breast cancer growth and metastasis through reactive oxygen species mediated mechanisms

Abstract: Accumulation of reactive oxygen species (ROS) has been implicated in induction of apoptosis and regulation of key signaling molecules in cancer cells. Phytochemicals are potent source of anticancer drugs as wells as potential inducers of ROS. Neem (Azadirachta indica) is a medicinal plant used for the treatment of various diseases. The main objective of this study is to investigate the anticancer effect of desacetyl nimbinene (DAN; an active ingredient of neem) against breast cancer. Normal and breast cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) is an important signaling pathway that is involved in tumor cell growth, proliferation, apoptosis, metabolism, angiogenesis, metastasis and immunity [810]. It also has a close connection with the NF-κB signaling pathway, in which the phosphorylation of Akt can activate NF-κB [11], triggering the regulation of downstream MMP-2 and MMP-9, regulating cancer cell proliferation, migration and invasion [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) is an important signaling pathway that is involved in tumor cell growth, proliferation, apoptosis, metabolism, angiogenesis, metastasis and immunity [810]. It also has a close connection with the NF-κB signaling pathway, in which the phosphorylation of Akt can activate NF-κB [11], triggering the regulation of downstream MMP-2 and MMP-9, regulating cancer cell proliferation, migration and invasion [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies deciphering the anti-metastatic effects of phytochemicals have shown sodium danshensu significantly inhibits the migration and invasion of human oral cancer cells by downregulating the phosphorylation of p38 [ 21 ]. Similarly, other bioactive plant compounds, such as Kahweol acetate and desacetylnimbinene, have been shown to inhibit cancer metastasis by reducing the phosphorylation of p38 [ 22 , 23 ]. All these observations are in line with our findings, which justify the significant involvement of p38 signaling pathway in mediating anti-metastatic effects of platyphyllenone [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that extract of neem leaves has bioactivity which can inhibit the growth of cancer cells [1]. Desacetylnimbin is one of the compounds in the extract of neem leaves which can prevent the growth of breast cancer cells through apoptosis mechanism [2]. Azadirachtin has potential as an inhibitory compound for the growth of cervical cancer cells [3].…”
Section: Introductionmentioning
confidence: 99%